2005
DOI: 10.1210/en.2005-0365
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Inducible Factor-1-Mediated Activation of Stanniocalcin-1 in Human Cancer Cells

Abstract: Stanniocalcin-1 (STC1) is an endocrine hormone originally discovered in the corpuscles of Stannius, endocrine glands on kidneys of bony fishes, and also has been identified in mammals. The mammalian STC1 gene is widely expressed in various tissues and appears to be involved in diverse biological processes. There is growing evidence to suggest that altered patterns of gene expression have a role in human cancer development. Recently STC1 has been identified as a stimulator of mitochondrial respiration and has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
90
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(98 citation statements)
references
References 43 publications
6
90
0
2
Order By: Relevance
“…Indeed, it has been shown that STC1 expression is markedly increased in hypoxia, common phenomenon that occurs in region of most solid human tumor in the latter stage of carcinogenesis (Gerritsen , 2002). STC1 expression would be induced by Hypoxia-inducible factor 1a (Yeung et al, 2005) and by vascular endothelial growth factor (Holmes and Zachary, 2008). Therefore, its increased level by miR-101b downregulation after HMGA1 induction might have an important role in the progression step of carcinogenesis in several human neoplasias all featured by HMGA1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that STC1 expression is markedly increased in hypoxia, common phenomenon that occurs in region of most solid human tumor in the latter stage of carcinogenesis (Gerritsen , 2002). STC1 expression would be induced by Hypoxia-inducible factor 1a (Yeung et al, 2005) and by vascular endothelial growth factor (Holmes and Zachary, 2008). Therefore, its increased level by miR-101b downregulation after HMGA1 induction might have an important role in the progression step of carcinogenesis in several human neoplasias all featured by HMGA1 overexpression.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the upregulation of STC1 by other stimuli reduces cell survival, we induced hypoxia with cobalt chloride because hypoxia had previously been found to induce STC1 expression in cancer cells (Zhang et al, 2000;Yeung et al, 2005). As in the cancer cells, STC1 mRNA expression was induced in STC1 þ / þ MEFs by hypoxia (Supplementary Figure S3A), and we found that STC1À/À MEFs exhibited greater survival than STC1 þ / þ MEFs (Supplementary Figure S3B).…”
Section: Regulation Of Oxidative Stress Response By Stc1 a Nguyen Et Almentioning
confidence: 66%
“…STC1 is a stress gene; it responds to various stimuli, including hypoxia 35 and cytokines. 36 The expression of STC1 after I/R is likely a response to the resulting hypoxia and/or release of cytokines; however, previous work showed that stress-induced expression of STC1 may lag considerably, 36 as does the expression of UCPs in response to STC1.…”
Section: Discussionmentioning
confidence: 99%